The Problem of Inclusion in Deliberative Environmental Valuation. (1st April 2017) - Vargas, Andrés; Lo, Alex; Howes, Michael; Rohde, Nicholas
Abstract : The idea of inclusive collective decision-making is important in establishing democratic legitimacy, but it fails when citizens are excluded. Stated-preference methods of valuation, which are commonly used in economics, have been criticised because the principle of willingness to pay may exclude low-income earners who do not have the capacity to pay. Deliberative valuation has been advocated as a way to overcome this problem, but deliberation may also be exclusive. In this review, two deliberative valuation frameworks are compared. The first is grounded on the idea of rational discourse that emphasises argument at the expense of other communicative strategies. It seeks to secure inclusion through procedural rules and prerequisites, but fails to address the underlying democratic limitation of argumentation. The second does not rely on the distinction between rational and rhetorical speech, and therefore admits alternative forms of communication. This approach recognises differences in the communicative capacities and practices of those who take part in deliberation, and so is better equipped to improve, though not to guarantee, inclusion.